Pemberdayaan Pekerja Migran: Peran BP3MI (Balai Pelayanan Perlindungan Pekerja Migran Indonesia) Provinsi Sumatera Barat dalam Meningkatkan Kesejahteraan Pekerja Migran Indonesia - Delvian Narendra; Resti Melani; Shifa Aishahila; Yulia Hanoselina; Rahmadhona Fitri (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
This article discusses the strategy of empowering Indonesian migrant workers through the role of BP3MI in improving the welfare of Indonesian migrant workers. This research uses a qualitative method with an interview approach and literature study to obtain data and a comprehensive picture of efforts to protect, empower, and improve the quality of life of migrant workers. In addition, the article also discusses the challenges faced, such as the high number of illegal migrant workers and the need for legal protection and adequate access to information for migrant workers. It is hoped that, through the role of BP3MI and the enforcement of official procedures, the welfare of migrant workers can be optimally improved and their rights thoroughly protected.